Bugs! - McKissack, Pat, 1944-; Martin, Clovis; McKissack, Fredrick (Chicago : Childrens Press, 1988)
Simple text and illustrations of a variety of insects introduce the numbers one through five.
Includes a word list.
Booklist.
Booklist, July 2005.
1.
1.4
K-3
Keywords: Counting; Insects -- Fiction; Counting; Insects -- Fiction; Readers (Elementary).